Superfetation or Arrested Embryonic Development of the Cat? - Galic, Ivan; Stancic, Ivan; Spasojevic, Jovan; Toholj, Bojan; Nikolić, Sandra; Kovacevic, Zorana (Acta Scientiae Veterinariae, 2024)
Background: If eggs are fertilized in different estrous cycle periods, such phenomenon is called superfetation. This phenomenon is occurred when an already pregnant animal manifests estrus (super-estrus), and mating in that estrus is fertile. Common criteria for assuming a case of superfetation includes the finding of malformed cubs in the uterus during ovariohysterectomy or delivery after a shorter birth interval than the expected length of pregnancy was. This report presents a rare case of different embryonic/fetal phases of kittens, diagnosed during emergency ovariohysterectomy due to pathological vaginal discharge. Case: A 2-year-old domestic cat was brought for clinical examination due to vaginal discharge. According to the anamnestic data, the cat was not in the pregnancy status. The vaginal secretion was deviated from characteristic physiological color and smell, and the vaginal examination revealed open cervix with no fetus in the birth canal. An ultrasound examination confirmed the pregnancy and also differences in size and structure of the gestational sacs. One ultrasound finding showed the existence of developed fetus, while the other finding showed only the gestational sac of the embryonic stage of pregnancy. Since no cardiac activity was observed of the developed fetus and because of presence of vaginal discharge, ovariohysterectomy was performed. The autopsy of uterus reported differently developed fetuses. Embryonic and fetal phases of fetuses were recorded inside one pregnant uterus of the cat. Discussion: If superfetation occurs, fertilization must occur after the tertiary follicles have been induced to ovulate by copulatory behavior of the pregnant animal. Cats can exhibit copulatory behavior similar to estrus during pregnancy, without a significant increase in serum estradiol or luteinizing hormone (LH), suggesting that such activity may not be related to endocrinology or reproductive physiology. In the case of induced/provoked ovulation which cats have, mating is not only necessary for depositing sperm, but also for activating ovulation. In the presence of an active corpus luteum, it is not clear whether copulation can induce ovulation. Therefore, superfetation cannot be assumed, but also not excluded, based on observed copulations during pregnancy. Furthermore, superfetation has never been definitively demonstrated in domestic cats, despite case reports which reported kittens in different stages in uterus. It has been reported in mice with superfetation that implantation zones of new embryos were often located at the caudal end of the uterine horn, near the cervix. In the present case report, the same phenomenon was noted in cat, where less developed gestational sac of the embryonic phase of the fetus was visible caudally. Due to this fact, there was space remained at the cranial end of the uterus for continued implantation of older fetus. In the current case, because the patient did not get to the physiological term of delivery and neither did 2 separate deliveries in shorter period of time, superfetation was not clearly distinguished from the arrested development of fetuses. In one case report, with also presented differently developed fetuses in the uterus of a pregnant cat, the cat was also diagnosed with paraplegia, which caused dystocia. There was also ovariohysterectomy performed, so it cannot be concluded whether a 2 nd birth would take place in the following period. The phenomenon of superfetation has been used to denote a condition in which the uterus contains embryos of different stages of development. Such findings also could be the result of the pathological conditions in which the growth and development of fetuses do not occur in the uterus, so it could not be said with certainty that was a case of superfetation. According to mentioned above, it could be concluded that the findings of differently developed fetuses were more likely to correspond with delayed development of the embryo than to superfetation, but this cannot be asserted with certainty either. Keywords: reproduction, ovariohysterectomy, super-estrus.